1997
DOI: 10.2307/3284267
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of an Aminopeptidase during Transition of Third- to Fourth-Stage Larvae of Ascaris suum

Abstract: Protease activity was identified in culture fluids collected during in vitro development of L3 to L4 larval stages of Ascaris suum. Fluorogenic peptide substrates with unblocked N-termini were specifically hydrolyzed indicating aminopeptidase activity; a terminal arginyl residue was preferred. Culture fluids did not hydrolyze fluorogenic peptide substrates with blocked N-termini (endopeptidase substrates). The aminopeptidase activity was inhibited by 1,10-phenanthroline (metalloprotease inhibitor) and by amast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…They aid in organ penetration by digesting the connective tissue matrix, provide an immunoprotective mechanism, are anticoagulants, facilitate larval molting, and play a major role in external digestion and nutrient uptake by the parasites (Knox & Kennedy, 1988;Moczoń & Wranicz, 1999). A similar role is played by other, nonproteolytic enzymes within the SP, including hyaluronidases (Hotez et al, 1994), leucine-aminopeptidase (Rhoads et al, 1997), acetylocholinesterases (Opperman & Chang, 1992) and other hydrolases (Dziekońska-Rynko et al, 2003). Studies by Dziekońska-Rynko and Rokicki (2005) failed to document the presence of endoproteases in the SP products from adult C. rudolphi, but high levels of leucineaminopeptidase, and different esterases and glycosidases were detected.…”
Section: Discussionmentioning
confidence: 99%
“…They aid in organ penetration by digesting the connective tissue matrix, provide an immunoprotective mechanism, are anticoagulants, facilitate larval molting, and play a major role in external digestion and nutrient uptake by the parasites (Knox & Kennedy, 1988;Moczoń & Wranicz, 1999). A similar role is played by other, nonproteolytic enzymes within the SP, including hyaluronidases (Hotez et al, 1994), leucine-aminopeptidase (Rhoads et al, 1997), acetylocholinesterases (Opperman & Chang, 1992) and other hydrolases (Dziekońska-Rynko et al, 2003). Studies by Dziekońska-Rynko and Rokicki (2005) failed to document the presence of endoproteases in the SP products from adult C. rudolphi, but high levels of leucineaminopeptidase, and different esterases and glycosidases were detected.…”
Section: Discussionmentioning
confidence: 99%
“…In Ascaris suum, a 293-kDa aminopeptidase was shown to be released into culture¯uid during development of L3 to L4 in vitro, with the peak level of secretion temporally associated with molting (Rhoads et al 1997). A role for a cysteine protease in the development of A. suum from L3 to L4 was also suggested by studies demonstrating the inhibition of this development by Z-phe-ala-FMK, a speci®c inhibitor of the cysteine class of proteases .…”
Section: Introductionmentioning
confidence: 88%
“…Proteases from other parasites have been shown to be involved in this essential process of moulting. Aminopeptidase activity was identified during in vitro development of the L3 to L4 larval stages of Ascaris suum (Rhoads et al 1997), and peak secretion of the enzyme was correlated with moulting, thus demonstrating its involvement. Metalloproteases of H. contortus (Gamble et al 1996) and metalloproteases associated with cysteine proteases of Dirofilaria immitis (Richer et al 1992) have also been suggested to play a role in the moulting process and in the degradation of cutaneous tissue components.…”
Section: Discussionmentioning
confidence: 98%